Search for D0-D0 mixing and branching-ratio measurement in the decay D0-->K+ pi- pi0. - Aubert, B; Barate, R; Bona, M; Boutigny, D; Couderc, F; Karyotakis, Y; Lees, J; Poireau, V; Tisserand, V; Zghiche, A; Grauges, E; Palano, A; et al. (2006)
We analyze 230.4 fb;{-1} of data collected with the BABAR detector at the PEP-II e;{+}e;{-} collider at SLAC to search for evidence of D0-D[over ];{0} mixing using regions of phase space in the decay D;{0}-->K;{+}pi;{-}pi;{0}. We measure the time-integrated mixing rate R_{M}=(0.023_{-0.014};{+0.018}(stat.)+/-0.004(syst.))%, and R_{M}<0.054% at the 95% confidence level, assuming CP invariance. The data are consistent with no mixing at the 4.5% confidence level. We also measure the branching ratio for D;{0}-->K;{+}pi;{-}pi;{0} relative to D;{0}-->K;{-}pi;{+}pi;{0} to be (0.214+/-0.008(stat.)+/-0.008(syst.))%.